The Organization of Educational Financing at Nuril Huda Islamic Junior High School Semarang Regency - Winda Silvana; Qoniatu Listianingsih; Atie Widiati (Journal of Transdisiplinary Studies in Education, 2026)
Background: The organization of educational financing plays an important role in ensuring that school programs run effectively and sustainably. In madrasahs, financial management requires clear coordination among school leaders, treasurers, and other stakeholders to support educational quality. Despite its importance, studies discussing how educational financing is organized in Islamic schools are still limited. Aims: This study aims to describe and analyze the organization of educational financing at Nuril Huda Islamic Junior High School, Semarang Regency, particularly regarding organizational structure, task allocation, coordination mechanisms, and financial administration. Methods: This study employed a qualitative approach using a single case study design. Data were collected through in-depth interviews, observations, and document analysis involving the principal, the school treasurer, and representatives of the school committee. The data were analyzed descriptively to obtain a comprehensive understanding of financing management practices. Result: The findings reveal that educational financing at Nuril Huda Islamic Junior High School has been organized systematically through a clear distribution of responsibilities among the principal, treasurer, teachers, and school committee members. Financial management is implemented collaboratively through the preparation of the School Activity and Budget Plan (RKAM) and supported by digital administrative systems. However, several challenges remain, including limited financial resources and the need to adapt to changing administrative regulations. Conclusion: Overall, the organization of educational financing has been implemented effectively and contributes to the continuity of educational activities and the improvement of educational quality in the madrasah.